The chemical investigation of commercial Chlorella variegatus Beijerinck (Fam. Oocystaceae) - De Ocampo, Esperanza F. Javier 1935-
Chemical investigation of the dried powder of Chlorella variegatus Beijerinck has resulted in the isolation of three types of principles: a fatty acid, fat-soluble vitamins and protein-carbohydrate complexes. Physical and chemical characterizations made identified these constituents to be palmitic acid m.p. 64(degrees C), vitamins which could be A and D and pectic-protein complexes.
Available to the general public.
Thesis (Master of Science in Pharmaceutical Chemistry)--University of the Philippines, 1976.
Keywords: Chlorella -- Analysis; Botany, Medical; Herbs--Therapeutic use